The Evolution of Forensic Medicine in the Digital Era: Enhancing Evidence Collection and Analysis - Dr. Suhas.S,; Dr. Lokesh. S,; Pradeep Kumar H S, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The field of forensic medicine has experienced a significant transformation with the integration of digital technologies. These advancements have redefined evidence collection, analysis, and interpretation, improving accuracy and efficiency. This review explores the evolution of forensic medicine in the digital era, focusing on technologies like digital imaging, artificial intelligence, and data analytics. It highlights their applications, benefits, and challenges, supported by recent research and case studies. Tables, graphs, and diagrams provide a comprehensive understanding of these innovations.